ELABORATING RECOMMENDATIONS FOR IMPROVING THE INSTITUTIONAL ENVIRONMENT OF THE RUSSIAN FEDERATION EDUCATION SYSTEM - A. V. Timiryasova (Russian Journal of Economics and Law)
Objective: To elaborate proposals for improving institutional environments of the Russian educational system. Methods: institutional and systemic. Results: It is revealed that the institutional environment development and innovative activity increase become the powerful drivers for international competitiveness and economic growth of Russia, and solving of these problems to a large extent depends on transformations in educational sphere. The ways are proposed of solving the problems of inefficient state property utilization in state educational establishments, basing on managerial business-technologies and state-private partnership. Scientific novelty: Segmenting of institutional environment of educational sphere is proposed and grounded by the capital structure of educational establishments and by stages of its forming and utilization. Characteristics are given to the partitioned segments. The main directions are proposed for improving the institutional environment of educational sphere in Russia (by partitioned segments) basing on the theory of intellectual capital management taking into account the Russian peculiarities. Practical value: The proposed segmenting of institutional environmet of educational sphere by the capital structure of educational establishments and by stages of its forming and utilization is intended for practical managers in the process of managing the educational establishment and educational sphere as a whole.